Evaluation of the Climate Village Program (Proklim) in Pete Village Tigaraksa District Tangerang Regency - Ellenza, Novalda Rahma; Handayani, Riny (Program Studi Ilmu Administrasi Negara FISIP UNPATTI, 2025)
The implementation of the Climate Village Program (Proklim) is a manifestation of the government effort to overcome climate change as stated in PermenLHK No.84 of 2016 concering the Climate Village Program. On of the villages that participated in the implementation of Proklim id Pete Village RW.05 in Tigaraksa District, Tangerang Regency. The purpose of this study is to evaluate the Climate Village Program in Pete Village, Tigaraksa District, Tangerang Regency, Banten Province. The theory used is Leo Agustino’s evaluation theory. This study uses a descriptive qualitative method. The result of the study show that the implementationof Proklim in Pete Village is stillnot optimal. the competence of the supervisors and coordinator of Proklim activities is good. However, the understanding of the community implementing the activity regarding the meaning of the regulation, both definition and objectives og Proklim, is still lacking because they only understand it as a reforestation activity. Supporting facilities in KWT activities are still minimal, in addition, there is no scheduled monitoring and evaluatuin carried put by the Tangerang Regency DLHK of the Proklim location.